Pengaruh Penerapan Modernisasi Sistem Administrasi Perpajakan Dan Kesadaran Wajib Pajak Terhadap Tingkat Kepatuhan Wajib Pajak Pada Kantor Pelayanan Pajak Pratama Jakarta Koja - Suffaeroh, Siti; Sari, Mira Permata (Jurnal Ilmu Administrasi Publik, 2024)
The implementation of the Modernization of the Tax Administration System which covers the areas of organizational structure, Business Process and Information and Communication Technology, human resource management (HR) and the implementation of good governance is the government's effort to increase the level of taxpayer compliance. In addition to the tax administration system, taxpayer awareness is one of the factors that influence the level of taxpayer compliance. The purpose of this study was to determine and analyze the effect of Modernization of the Tax Administration System and Taxpayer Awareness on the Compliance Level of Individual Taxpayers at the Jakarta Koja Primary Tax Service Office. This research method uses a quantitative descriptive approach. Respondents in this study were 100 individual taxpayers using nonprobability sampling technique. Methods of data analysis in this study using multiple linear regression analysis. The conclusion from the results of this study is that there is a positive and significant influence on the implementation of modernization of the tax administration system and awareness of taxpayers on individual taxpayer compliance at KPP Pratama Koja.